The Shaker Experience in America: A History of the United Society of Believers - Reid-Maroney, Nina (Labour / Le Travail, 1994)
The article reviews the book, "The Shaker Experience in America: A History of the United Society of Believers," by Stephen Stein.
Keywords: BOOKS – Reviews; Nonfiction; SHAKER Experience in America: A History of the United Society of Believers; The (Book); SHAKERS; STEIN; Stephen